EFISIENSI PERUSAHAAN KONSTRUKSI DI INDONESIA - Beny Mulyana Sukandar; Noer Azam Achsani; Roy Sembel; Bagus Sartono (Universitas Mercu Buana, 2018)
Along with the increase in government programs to accelerate infrastructure development, the construction industry in Indonesia has faced intense competition which has forced construction companies in Indonesia to be efficient in order to remain profitable. This study is aimed to measure the efficiency of construction companies in Indonesia. Data Envelopment Analysis (DEA)is used for the research method and data is obtained from the companies’ yearly report in the period 2010-2016 listed in the Indonesia Stock Exchange. The results of the study show that state-owned enterprises (BUMN) are more efficient than private companies. This is due to the large number and value of the project from the government in the field of infrastructure. The study has important implications for the the government to warn state owned companies to stay efficient yet profitable when facing foreign competitions. Since the study showed that companies with large revenue (sales) and low cost are efficient. The private companies ought to seek bigger sales from government projects